BANK CREDIT GROWTH IN INDONESIA DURING THE COVID-19 PANDEMIC AND ITS REGULATIONS - Aziz, Abdul; Maulida, Sri (Journal of Central Banking Law and Institutions, 2024)
Credit growth related to production, consumption, investment, exports, and imports is considered crucial for economic growth. The Covid-19 pandemic has had a major impact on the economies of countries in the world, as seen from a significant decline in credit growth. This study examines the effects of Economic Growth, Exchange Rate, Inflation, BI Rate, Third Party Funds (TPF), and Non-Performing Loans (NPL) on Banking Credit Growth in Indonesia during the COVID-19 Pandemic Period and regulations issued during that period. Analysis using multiple linear regression method using EViews 10 software with data type in the form of time series. The results of this study showed that only TPF growth had a significant effect. Simultaneously, the variables of Economic Growth, Exchange Rate, Inflation, BI Rate, NPL and Deposit Growth have a significant effect. The most dominantinfluencing variable is deposit growth.